Associations Between Drosophila suzukii (Diptera: Drosophilidae) and Fungi in Raspberries. Issue 1 (6th December 2018) - Lewis, M T; Koivunen, E E; Swett, C L; Hamby, K A
Abstract: The invasive vinegar fly, Drosophila suzukii Matsumura, has emerged as one of the most serious arthropod pests of primocane red raspberries ( Rubus ideaus L.) in the United States. In raspberries, D. suzukii encounter a diverse community of microbes, including fruit rot pathogens such as Botrytis cinerea Pers and Cladosporium cladosporioides de Vries. In this study, our primary objectives were to evaluate D. suzukii– fungal associations and determine D. suzukii 's influence on fungal communities in raspberry fruit. Through culture-based surveys of larval gut microbes, we isolated several yeast fungi (primarily Hanseniaspora spp.), as well as Cladosporium, Botrytis, and several other non-yeast fungi from larval frass, suggesting that D. suzukii larvae encounter and feed on these fungi. Subsequent field surveys confirmed that D. suzukii larvae occurred in berries affected by Botrytis fruit rot and Cladosporium fruit rot. Under laboratory conditions, D. suzukii may facilitate C. cladosporioides infections, likely through the introduction of epiphytic propagules on the fruit surface. We could not detect impacts on B. cinerea infections or establish a clear vectoring relationship for either fruit rot. These studies provide evidence for an association between D. suzukii and fungal fruit rot pathogens. Understanding interactions between raspberry fruit, D. suzukii, and fungal microbes—especially whether D. suzukii facilitates the development of fruit rots or conversely, if fruit rots influence D. suzukii infestation patterns—may improve pest and pathogen management programs.